The loss of polyphenol oxidase function is associated with hilum pigmentation and has been selected during pea domestication. Issue 5 (10th June 2022) - Balarynová, Jana; Klčová, Barbora; Sekaninová, Jana; Kobrlová, Lucie; Cechová, Monika Zajacová; Krejčí, Petra; Leonova, Tatiana; Gorbach, Daria; Ihling, Christian; Smržová, Lucie; Trněný, Oldřich; Frolov, Andrej; et al.
Summary: Seed coats serve as protective tissue to the enclosed embryo. As well as mechanical there are also chemical defence functions. During domestication, the property of the seed coat was altered including the removal of the seed dormancy. We used a range of genetic, transcriptomic, proteomic and metabolomic approaches to determine the function of the pea seed polyphenol oxidase ( PPO ) gene. Sequencing analysis revealed one nucleotide insertion or deletion in the PPO gene, with the functional PPO allele found in all wild pea samples, while most cultivated peas have one of the three nonfunctional ppo alleles. PPO functionality cosegregates with hilum pigmentation. PPO gene and protein expression, as well as enzymatic activity, was downregulated in the seed coats of cultivated peas. The functionality of the PPO gene relates to the oxidation and polymerisation of gallocatechin in the seed coat. Additionally, imaging mass spectrometry supports the hypothesis that hilum pigmentation is conditioned by the presence of both phenolic precursors and sufficient PPO activity. Taken together these results indicate that the nonfunctional polyphenol oxidase gene has been selected during pea domestication, possibly due to better seed palatability or seed coat visual appearance.